Adsorção de Pb (II), Cd (II) E Cu (II) em argila caulinítica natural e argila natural contendo montmorilonita - Aragão, Débora Martins (2012)
The contamination by toxic metals has been a serious environmental problem. Many researches have been developed with the objective the environmental remediation. The adsorption has been one of the most used process by researchers to remove metals in recent years. In this work, it was studied the use of natural clays of the state of Sergipe, with high levels of kaolinite and montmorillonite as adsorbent materials to remove Pb (II), Cd (II) and Cu (II) in aqueous solution. It was investigated the adsorption conditions including contact time, pH and adsorption isotherms. Using kaolinite equilibrium of adsorption for the three metals was reached at about 30 min, and a contact time of 60 min was chosen. In the beginning of study was conducted at pH of metal nitrate solutions (pH 5.2 ± 0.2) resulting in a maximum removal of 86.0 %, 43.2 % and 34.3 % for Pb (II), Cd (II) and Cu (II) respectively. The pH 7.0 was determined to be the most efficient for the removal of Pb (II) ( 99.9 %), Cd (II) (82.9 %) and Cu (II) (97.9 %). The Langmuir isotherm was the model with the best fit to the adsorption data obtained for the three metals, with Qo of 1.511 mg g-1 for Pb (II); 0.853 mg g-1 for Cd (II) and 0.417 mg g-1 for Cu (II). In the application of natural clay containing montmorillonite, it was obtained; high removal percentages for Pb (II), Cd (II) and Cu (II). The adsorption equilibrium was reached in the first minutes and the contact time of 30 min was selected, with maximum adsorption of 99.54 %; 93.37 %; 99.48 % for Pb(II), Cd (II) and Cu (II) in natural pH of metal in the pH (pH 5.2 ± 2). In pH study, it was observed that the pH variations did not alter significantly the adsorption of metals. Among the models applied, Langmuir was the best fitted one for the three adsorbents applied in this work with Qo of 6.98 mg g-1 1.48 mg g-1 and 2.07 mg g-1 for Pb (II), Cd (II) and Cu (II) respectively. The results show clays that have high levels either kaolinite or montmorillonite show appropriate features for application in the process of adsorption of Pb (II), Cd (II) and Cu (II).